Peningkatan Pengetahuan Kadet Mahasiswa UNHAN RI tentang Kesiapsiagaan Bencana dan Mental Recovery Pasca Bencana - Lila Irawati T.W; Hanifah Hanifah; Karen Afian; Zulfa Diana Husna; Ihsan Fauzi Nurfakhriy; Muhammad Raihan; Radyarza Bagus; Ferdinand Beatrix; Mochmmad Hendik Widy Awan; Elies Fitriani (Universitas Malahayati Lampung, 2026)
ABSTRACT Mental health issues in Indonesia have increase. There has also been an increase in behavioral and emotional problems post-pandemic. Disasters such as fires have the potential to trigger long-term stress and trauma, while the level of public understanding of disaster preparedness and initial psychological support is still low. Unhan student cadets are studying on scholarships at the Defense University with the aim of being placed in 3T areas. Cadets’ must have sufficient knowledge regarding disaster preparedness and management as well as mental recovery after a disaster. After socialization and demonstrations on disaster preparedness, especially fire disasters and mental health management for Unhan RI student cadets, there are an increase in knowledge about disaster preparedness and mental recovery after disaster with preposttest score significancy level p0.05. Counseling and demonstration of fire disaster management for Unhan RI students from BNPB and Damkar District Citereup. Keywords: Disaster Preparedness, Mental Recovery, Cadets, Disaster Management. ABSTRAK Masalah kesehatan mental di Indonesia turut menunjukkan peningkatan. Terdapat peningkatan juga terkait dengan masalah perilaku dan emosional pascapandemi. Bencana seperti kebakaran berpotensi memicu stres dan trauma jangka panjang, sementara tingkat pemahaman masyarakat mengenai kesiapsiagaan bencana dan dukungan psikologis awal masih rendah. Kadet mahasiswa Unhan menempuh Pendidikan beasiswa di Universitas Pertahanan dengan tujuan penempatan di daerah 3T. Pengetahuan kadet harus cukup memadai terkait dengan kesiapsiagaan serta penanganan bencana sekaligus mental recovery pasca bencana. Setelah sosialisasi dan demo tentang kesiapsiagaan bencana khususnya bencana kebakaran dan penanganan kesehatan mental kepada kadet mahasiswa Unhan RI terdapat peningkatan pengetahuan tentang kesiapsiagaan bencana mental recovery pasca bencana dilihat dari peningkatan skor pre-postest dengan nilai signifikansi p0.05. Penyuluhan dan demonstrasi penanganan bencana kebakaran bagi mahasiswa Unhan RI dari BNPB dan Damkar Distrik Citereup. Kata Kunci: Kesiapsiagaan Bencana, Mental Recovery, Kadet, Manajemen Bencana.